Monitoring AICCRA-Ghana intervention sites for One Health compliance - Stenrød, Marianne; Almvik, Marit; Eiken, Hans Geir; Elameen, Abdelhameed; Fløystad, Ida Marie Bardalen; Havranek, Ivo; Lang, Kathinka; Odenmarck, Sven Roar; Osae, Michael Yao; Offei, Benjamin Kwasi (Accelerating Impacts of CGIAR Climate Research for Africa, 2023)
In strict adherence to the World Bank’s Environmental and Social Framework (ESF) as well as the applicable legal and regulatory frameworks of Ghana for the pilot of CSA innovations, it is important to monitor the environmental impact of CSA innovation and ensure they pose no harm to the health of humans, animals, plants and their shared environment. This to ensure that all IACCRA intervention sites in Ghana are One Health sensitive. This report documents the sampling and analysis of a set of relevant chemical and biological parameters in environmental samples from the AICCRA-Ghana pilot sites for CSA innovations.